Images of the North: An Analysis of Book Covers of Swedish Crime Fiction in Greek and Spanish Translation - Smaragdi, Marianna; Johansson, Ingela (Lund University, 2020)
This study is an analysis of the book cover images of a selection of Swedish crime literature, published in Greece and the Spanish-speaking world in the period of 2000-2017. Covers are crucial to the paratextual signal system (Genette, 1991); departing from theories on paratext within translation studies, we aim to compare the original book covers to the covers of the translated volumes. Do the Greek and Spanish book markets emphasise the stereotypical images of the North that have been identified in studies on borealism (Chartier, 2008)? The image covers of the original and the translated editions were examined by means of a content analysis, complemented by an empirical study. The empirical study consist of anonymously answered questionnaires with questions about the book covers as well as the anonymous respondents’ background information. The examination of the sample did not unambiguously indicate that the translated editions draw more heavily on the Nordic origin. Similarly, not all covers of the translations revealed belonging to the crime genre.

I denna studie analyseras bokomslag från ett urval av svensk kriminallitteratur publicerad i Grekland och den spansktalande världen från perioden 2000-2017. Bokomslag är viktiga paratexter (Genette, 1991), och med avstamp i teorier om paratext inom översättningsstudier avser vi att jämföra de svenska bokomslagen med omslagen till de översatta volymerna. Betonas stereotypa bilder av Norden, såsom de har beskrivits inom borealismen (Chartier, 2008), i de grekiska och spanskspråkiga bokmarknaderna? Vi har undersökt bokomslagen till de svenska och översatta utgåvorna genom att göra en innehållsanalys på dem, och kompletterat denna med en empirisk studie. Den empiriska studien består av anonyma enkäter med frågor om såväl bokomslagen och bakgrundsinformation som respondenterna. Undersökningen visade inte entydigt att de översatta utgåvorna anspelade i högre grad på det nordiska. Den visade också att de översatta volymernas omslag inte alltid i större omfattning angav tydlig genretillhörighet.
Bilder av Norden: En analys av bokomslag till svensk kriminallitteratur i grekisk och spansk översättning
Keywords: borealism; borealism; paratext; paratext; Swedish crime; svensk kriminallitteratur; Book covers; bokomslag; translations; översättningar; imagology; imagologi; Cultural activities and participation; Kulturaktiviteter och deltagande; Languages and Literature; Språk och litteratur; Studies of Specific Literatures; Litteraturstudier